MULTIFUNCTIONAL BIOACTIVITY OF Mangifera indica SEED EXTRACT: ANTIMICROBIAL, ANTIOXIDANT, AND THERAPEUTIC POTENTIAL AGAINST UTI PATHOGENS - Abirami S; Rajalinga Malathi B; Kannan M; Sivapriyadarshini K (The Bioscan, 2026)
The present study investigates the antimicrobial, antifungal, anti-inflammatory, antioxidant, phytochemical, and antiproliferative properties of the ethanol extract of Mangifera indica (mango) seed, along with its chemical profiling using GC–MS analysis. Mango seeds were collected and processed to obtain ethanol extracts. Urine samples from patients with urinary tract infections (UTIs) were collected, and pathogenic bacteria were isolated and identified. The antibacterial activity of the extract was evaluated against these UTI pathogens. Additionally, fungal species were isolated from contaminated vegetables, and antifungal activity of the extract was assessed. The antioxidant potential of the extract was determined through standard assays, while anti- inflammatory activity was evaluated using protein denaturation inhibition. Enzyme inhibition studies, including α-amylase activity, were conducted to assess potential antidiabetic properties. The antiproliferative activity of the extract was analyzed to evaluate its potential against abnormal cell growth. Qualitative phytochemical screening was performed to identify bioactive constituents present in the extract. Furthermore, GC–MS analysis was carried out to characterize the chemical compounds responsible for the observed biological activities. The study also explored the application of mango seed extract in water quality assessment and as a potential food additive. The findings suggest that ethanol extract of Mangifera indica seed possesses significant bioactive properties, indicating its potential as a natural source for antimicrobial, therapeutic, and nutraceutical applications.